Qualitative Study: Mathematics Teachers' Strategies in Delivering Geometry Material in Inclusive Classes - Dhesta Kusuma Dewi, Tharienna (Aksioma Education Journal, 2025)
This study aims to explore geometry learning strategies used by mathematics teachers in inclusive classrooms at the junior high school level. Geometry, as part of the mathematics curriculum, has a high level of abstraction, thus demanding a pedagogical approach that is adaptive to the diversity of cognitive and socio-emotional functions of students, especially those with special needs. This study used a descriptive qualitative approach with data collection techniques such as in-depth interviews, classroom observations, and documentation studies. Data analysis was conducted based on the Miles and Huberman model, with attention to the qualitative validity principles of Lincoln and Guba. The findings indicate that teachers implement learning differentiation strategies through content modification, the use of multisensory media, assistive technology, and a collaborative project-based approach. This approach aligns with the principles of Universal Design for Learning and the theory of multiple intelligences that encourage instructional flexibility. However, limited pedagogical training, workload, and lack of institutional support are significant challenges. Teachers' critical reflection as reflective practitioners plays a crucial role in designing inclusive and contextual learning innovations. This study recommends strengthening teacher capacity through ongoing training and cross-stakeholder collaboration to achieve academic equity in inclusive mathematics education.